Children's learning from educational television : Sesame Street and beyond - Fisch, Shalom M. (LEA's communication series., 2004)
This title documents the impact of educational television in a variety of subject areas and proposes mechanisms to explain its effects. Drawing from a wide variety of research spanning several disciplines, author Shalom M. Fisch analyses the literature on the impact of educational resources.